Polycarbonate resin and molded products
The development of a polycarbonate resin composition using isosorbide, polytrimethylene ether glycol, and aliphatic or alicyclic dihydroxy compounds addresses the need for high biomass content and improved mechanical properties, achieving enhanced mechanical strength, heat resistance, and impact resistance.
Patent Information
- Application Number
- JP2021069560
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-04-16
AI Technical Summary
There is a need for polycarbonate resins with higher biomass content and improved mechanical strength and heat resistance, particularly in applications where stress concentration occurs, and existing solutions often rely on petroleum-based impact modifiers.
A polycarbonate resin composition that includes structural units derived from isosorbide, polytrimethylene ether glycol, and aliphatic or alicyclic dihydroxy compounds, with specific weight ratios and molecular weight ranges, to achieve enhanced mechanical properties and heat resistance while maintaining a high biomass content.
The resulting polycarbonate resin exhibits excellent mechanical strength, heat resistance, and impact resistance, while also achieving a high biomass content, making it suitable for sustainable applications.
Smart Images

Figure 0007658149000001 
Figure 0007658149000002 
Figure 0007658149000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polycarbonate resin and a molded article thereof having excellent mechanical strength and heat resistance. [Background technology]
[0002] Polycarbonate resins are generally made from bisphenols as monomer components, and taking advantage of their advantages such as transparency, heat resistance, and mechanical strength, they are widely used as so-called engineering plastics in the optical field, such as electrical and electronic components, automotive parts, optical recording media, and lenses. On the other hand, due to concerns about global warming caused by the depletion of petroleum resources and increased carbon dioxide emissions, there is a demand for the development of plastics made from carbon-neutral plant-derived monomers. In this context, polycarbonate resins produced using the plant-derived raw material isosorbide (hereinafter sometimes referred to as "ISB") have been developed in recent years and are beginning to be used in automotive parts, optical applications, and as a glass replacement (see, for example, Patent Documents 1 and 2).
[0003] Polycarbonate resins obtained from ISB not only have excellent optical properties, but also have extremely excellent weather resistance and surface hardness compared to conventional general-purpose aromatic polycarbonate resins. However, there is a demand for further improvements in mechanical properties such as tensile elongation and impact resistance in areas where stress is concentrated. To address this issue, for example, Patent Document 3 discloses a method for improving impact resistance by incorporating an elastomer into a polycarbonate resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2004 / 111106 Brochure [Patent Document 2] International Publication No. 2007 / 148604 Brochure [Patent Document 3] JP 2017-88774 A Summary of the Invention [Problem to be solved by the invention]
[0005] As disclosed in Patent Document 3, by blending an elastomer with a polycarbonate resin, excellent improvement in impact resistance can be expected, but in many cases, the materials used as impact improvers are derived from petroleum and other mainly non-renewable resources. In recent years, as the use of non-renewable resources is increasingly expected, society is demanding resins that have a higher biomass content and excellent practical properties. An object of the present invention is to provide a polycarbonate resin which has a higher biomass content and is excellent in mechanical strength and heat resistance. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above problems, the present inventors have found that a polycarbonate resin having excellent mechanical strength and heat resistance can be obtained by using a specific compound as a copolymerization component.
[0007] That is, the present invention relates to the following. [1] A polycarbonate resin comprising at least a structural unit (A) represented by the following formula (1), a structural unit (B) represented by the following formula (2), and a structural unit (C) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound, the polycarbonate resin containing 40% by weight or more and 80% by weight or less of the structural unit (A) and 1% by weight or more and 20% by weight or less of the structural unit (B), the number average molecular weight of the structural unit (B) being 1,200 or more and 5,000 or less.
[0008] [ka]
[0009] [ka]
[0010] In formula (2), n is an integer of 2 or more. [2] The polycarbonate resin according to [1], containing 1% by weight or more and 40% by weight or less of the structural unit (C). [3] The polycarbonate resin according to [1] or [2], containing, as the structural unit (C), 1 wt % or more and 40 wt % or less of a structural unit represented by the following formula (3):
[0011] [ka]
[0012] [4] The polycarbonate resin according to any one of [1] to [3], which has a glass transition temperature of 90° C. or higher and 140° C. or lower. [5] A molded article obtained by molding the polycarbonate resin according to any one of [1] to [4]. [6] A method for producing the polycarbonate resin according to any one of [1] to [4], comprising a step of polycondensing raw materials, via an ester exchange reaction, a dihydroxy compound forming the structural unit (A) represented by formula (1), a dihydroxy compound forming the structural unit (B) represented by formula (2), a dihydroxy compound forming the structural unit (C), and a monomer containing a diester carbonate, wherein the dihydroxy compound forming the structural unit (B) represented by formula (2) is polytrimethylene ether glycol, and the number average molecular weight of the polytrimethylene ether glycol is 1,200 or more and 5,000 or less. Effect of the Invention
[0013] The polycarbonate resin of the present invention has excellent mechanical strength and heat resistance, and therefore, by using such a polycarbonate resin, it is possible to obtain a high-quality molded product. In addition, the polycarbonate resin of the present invention has a high biomass content, and can contribute to the realization of a sustainable society. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified in any manner without departing from the gist of the present invention. In this specification, when "~" is used with a numerical value or a physical property value enclosed therein, the values before and after the "~" are included in the expression.
[0015] In this specification, the term "repeated structural unit" refers to a structural unit in which the same structure appears repeatedly in a resin, and each of the structural units is linked to form the resin. For example, in the case of a polycarbonate resin, the carbonyl group is also referred to as the repeating structural unit. In addition, the term "structural unit" refers to a partial structure that constitutes a resin, and a specific partial structure contained in the repeating structural unit. For example, it refers to a partial structure sandwiched between adjacent linking groups in a resin, or a partial structure sandwiched between a polymerizable reactive group present at the end of a polymer and a linking group adjacent to the polymerizable reactive group. More specifically, in the case of a polycarbonate resin, a carbonyl group is a linking group, and a partial structure sandwiched between adjacent carbonyl groups is referred to as a structural unit. In this specification, the weight ratio of each structural unit in the polycarbonate resin is calculated assuming that the total weight of all structural units and linking groups is 100% by weight.
[0016] [Polycarbonate resin] The polycarbonate resin of the present invention is a polycarbonate resin containing at least a structural unit (A) represented by the following formula (1) (hereinafter may be simply referred to as structural unit (A)), a structural unit (B) represented by the following formula (2) (hereinafter may be simply referred to as structural unit (B)), and a structural unit (C) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound (hereinafter may be simply referred to as structural unit (C)). The structural unit (A) is contained in an amount of 40% by weight or more and 80% by weight or less, and the structural unit (B) is contained in an amount of 1% by weight or more and 20% by weight or less, and the number average molecular weight of the structural unit (B) is 1,200 or more and 5,000 or less.
[0017] [ka]
[0018] [ka]
[0019] In formula (2), n is an integer of 2 or more.
[0020] Dihydroxy compounds forming the structural unit (A) include isosorbide (ISB), isomannide, and isoidet, which are stereoisomers. These may be used alone or in combination of two or more. Among them, isosorbide obtained by dehydration condensation of sorbitol produced from various starches, which are abundant and easily available as a plant-derived resource, is particularly preferred in terms of availability, ease of production, and properties of the resulting molded product (for example, heat resistance, impact resistance, surface hardness).
[0021] The weight ratio of the structural unit (A) in the polycarbonate resin of the present invention is 40% by weight or more and 80% by weight or less, and the lower limit is particularly preferably 45% by weight or more. The upper limit is more preferably 75% by weight or less, further preferably 70% by weight or less, and particularly preferably 65% by weight or less. Within the above range, a resin having an excellent balance between mechanical strength, heat resistance, and melt processability can be obtained.
[0022] As the dihydroxy compound forming the structural unit (B), polytrimethylene ether glycol (PO3G) is used. It is preferable to use PO3G with a biomass content of 100%, which is synthesized by condensing 1,3-propanediol produced from plant-derived raw materials. Whether isosorbide or PO3G is produced from plant-derived resources can be determined, for example, by radiocarbon ( 14 This can be confirmed by measuring the concentration of C).
[0023] PO3G having a number average molecular weight of 1200 or more and 5000 or less is used. The lower limit is more preferably 1500 or more, particularly preferably 1700 or more. The upper limit is more preferably 4000 or less, particularly preferably 3000 or less. When the number average molecular weight of PO3G is within the above range, the structural unit (B) which becomes the soft segment forms a microphase separation structure in the resin, and further has a moderate compatibility with the structural unit (A), so that adhesion at the phase interface is obtained and excellent impact resistance can be expressed. In addition, the average value (average polymerization degree) of n of the structural unit (B) in the polycarbonate resin is preferably 20 or more and 90 or less. The lower limit is more preferably 25 or more, particularly preferably 30 or more. The upper limit is more preferably 70 or less, particularly preferably 55 or less. The number average molecular weight and average polymerization degree of PO3G are calculated from the analysis of the hydroxyl value described later.
[0024] The weight ratio of the structural unit (B) in the polycarbonate resin of the present invention is 1% by weight or more and 20% by weight or less. The lower limit is more preferably 2% by weight or more, and particularly preferably 3% by weight or more. The upper limit is more preferably 15% by weight or less, and particularly preferably 12% by weight or less. Within the above range, a resin having an excellent balance between impact resistance and heat resistance can be obtained.
[0025] The characteristics of PO3G are explained by comparing it with similar compounds such as polyethylene glycol (PEG), polypropylene glycol (PPG), and polytetramethylene ether glycol (PTMG). PEG has good compatibility with structural unit (A), so it does not form a phase-separated structure, and its performance such as impact resistance is inferior to PO3G. PO3G has moderate compatibility with structural unit (A), and forms a phase consisting of PO3G structural units uniformly dispersed in microns, which shows excellent impact resistance. PPG, like PEG, has high compatibility with structural unit (A), and is difficult to form a phase-separated structure. In addition, PPG has the disadvantage of having a relatively low thermal decomposition temperature, and has poor thermal stability. PTMG has low compatibility with structural unit (A), which causes macroscopic phase separation, so high impact resistance cannot be obtained.
[0026] The polycarbonate resin of the present invention further contains a structural unit (C) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound. The polycarbonate resin of the present invention may simultaneously have a structural unit derived from an aliphatic dihydroxy compound and a structural unit derived from an alicyclic dihydroxy compound, in which case both structural units are collectively referred to as "structural unit (C)".
[0027] Examples of the aliphatic dihydroxy compound include the following dihydroxy compounds: straight-chain aliphatic dihydroxy compounds such as ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,5-heptanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol; and branched-chain aliphatic dihydroxy compounds such as 1,3-butanediol, 1,2-butanediol, neopentyl glycol, and hexylene glycol.
[0028] Examples of the alicyclic dihydroxy compound include the following dihydroxy compounds: dihydroxy compounds which are primary alcohols of alicyclic hydrocarbons, such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, tricyclodecane dimethanol, pentacyclopentadecane dimethanol, 2,6-decalin dimethanol, 1,5-decalin dimethanol, 2,3-decalin dimethanol, 2,3-norbornane dimethanol, 2,5-norbornane dimethanol, 1,3-adamantanedimethanol, and dihydroxy compounds derived from terpene compounds such as limonene; dihydroxy compounds which are secondary or tertiary alcohols of alicyclic hydrocarbons, such as 1,2-cyclohexanediol, 1,4-cyclohexanediol, 1,3-adamantanediol, hydrogenated bisphenol A, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol.
[0029] Among the above-mentioned aliphatic dihydroxy compounds or alicyclic dihydroxy compounds, from the viewpoint of an excellent balance between mechanical properties and heat resistance, alicyclic dihydroxy compounds are more preferred, 1,4-cyclohexanedimethanol and tricyclodecane dimethanol are even more preferred, and 1,4-cyclohexanedimethanol is particularly preferred.
[0030] The polycarbonate resin of the present invention preferably contains 1% by weight or more and 40% by weight or less of the structural unit (C) derived from an aliphatic dihydroxy compound or an alicyclic dihydroxy compound. The lower limit is more preferably 5% by weight or more, even more preferably 10% by weight or more, and particularly preferably 15% by weight or more. The upper limit is more preferably 35% by weight or less, and particularly preferably 30% by weight or less. Within the above range, a resin having an excellent balance between impact resistance and heat resistance can be obtained.
[0031] The polycarbonate resin of the present invention particularly preferably contains 1% by weight or more and 40% by weight or less of the structural unit represented by the following formula (3) as the structural unit (C), which can provide a resin with a better balance between impact resistance and heat resistance.
[0032] [ka]
[0033] The polycarbonate resin of the present invention may contain structural units other than the structural unit (A), the structural unit (B), and the structural unit (C) (hereinafter, sometimes referred to as "other structural units"). Examples of compounds forming other structural units include ether-containing dihydroxy compounds, acetal-containing dihydroxy compounds, aromatic-containing dihydroxy compounds, and diester compounds. In addition, polycarbonate resins partially incorporating structural units derived from diester compounds are called polyester carbonate resins. In this specification, polycarbonate resins include polyester carbonate resins.
[0034] As the ether-containing dihydroxy compound, for example, oxyalkylene glycols such as diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol can be used.
[0035] Examples of the acetal-containing dihydroxy compound that can be used include spiroglycol (also known as 3,9-bis(1,1-dimethyl-2-hydroxyethyl-2,4,8,10-tetraoxaspiro[5,5]undecane) and dioxane glycol (also known as 2-(1,1-dimethyl-2-hydroxyethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane).
[0036] Examples of the aromatic dihydroxy compound include the following compounds: 2-bis(4-hydroxyphenyl)propane, 2,2-bis(3-methyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-diethylphenyl)propane, 2,2-bis(4-hydroxy-(3-phenyl)phenyl)propane, 2,2-bis(4-hydroxy-(3,5-diphenyl)phenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, bis(4-hydroxyphenyl) Methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)pentane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, bis(4-hydroxyphenyl)diphenylmethane, 1,1-bis(4-hydroxyphenyl)-2-ethylhexane, 1,1-bis(4-hydroxyphenyl)decane, bis(4-hydroxy-3-nitrophenyl)methane, 3,3-bis(4-hydroxyphenyl)pentane, 1,3-bis (2-(4-hydroxyphenyl)-2-propyl)benzene, 1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, 1,1-bis(4-hydroxyphenyl)cyclohexane, bis(4-hydroxyphenyl)sulfone, 2,4'-dihydroxydiphenyl sulfone, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxy-3-methylphenyl)sulfide, bis(4-hydroxyphenyl)disulfide, 4,4 aromatic bisphenol compounds such as 4,4'-dihydroxydiphenyl ether and 4,4'-dihydroxy-3,3'-dichlorodiphenyl ether; dihydroxy compounds having an ether group bonded to an aromatic group such as 2,2-bis(4-(2-hydroxyethoxy)phenyl)propane, 2,2-bis(4-(2-hydroxypropoxy)phenyl)propane, 1,3-bis(2-hydroxyethoxy)benzene, 4,4'-bis(2-hydroxyethoxy)biphenyl, and bis(4-(2-hydroxyethoxy)phenyl)sulfone;9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxypropoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxypropoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxypropoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isobutylphenyl)fluorene , 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-cyclohexylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6-methylphenyl)fluorene, 9,9-bis(4-(3-hydroxy-2,2-dimethylpropoxy)phenyl)fluorene and other dihydroxy compounds having a fluorene ring;
[0037] Examples of the diester compound include the following compounds: aromatic dicarboxylic acids such as terephthalic acid, phthalic acid, isophthalic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, 4,4'-benzophenonedicarboxylic acid, 4,4'-diphenoxyethanedicarboxylic acid, 4,4'-diphenylsulfonedicarboxylic acid, and 2,6-naphthalenedicarboxylic acid; alicyclic dicarboxylic acids such as 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; and aliphatic dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid. These dicarboxylic acid components can be used as raw materials for polyester carbonate resins as dicarboxylic acids themselves, but depending on the production method, dicarboxylic acid esters such as methyl esters and phenyl esters, and dicarboxylic acid derivatives such as dicarboxylic acid halides can also be used as raw materials.
[0038] By using aromatic dihydroxy compounds or diester compounds such as bisphenol compounds as copolymerization components, the heat resistance of polycarbonate resins can be improved in some cases, but on the other hand, when the polycarbonate resin contains a large amount of aromatic structures, the weather resistance tends to decrease. In addition, since there is a large difference in the polymerization reactivity between bisphenol compounds or diester compounds and dihydroxy compounds forming the structural unit (A) or the structural unit (B), the bisphenol compounds or diester compounds remain unreacted or remain in the terminal groups, making it difficult to obtain a polycarbonate resin with a high molecular weight, and mechanical properties such as impact resistance tend to decrease. If the reaction temperature is raised to a high level in order to promote the reaction, the structural unit (A) is thermally decomposed, and the resulting polycarbonate resin tends to become colored. For these reasons, the content ratio of the structural unit derived from aromatic dihydroxy compounds or diester compounds is preferably 15% by weight or less, more preferably 10% by weight or less, and particularly preferably 5% by weight or less.
[0039] (carbonic acid diester) The linking group of the above structural unit contained in the polycarbonate resin of the present invention is introduced by polymerizing a carbonate diester represented by the following formula (4).
[0040] [ka]
[0041] (In formula (4), R 1 and R 2 each represents an aliphatic hydrocarbon group having 1 to 18 carbon atoms which may have a substituent, or an aromatic hydrocarbon group which may have a substituent, and R 1 and R 2 may be the same or different.)
[0042] R 1 and R 2 is preferably a substituted or unsubstituted aromatic hydrocarbon group, more preferably an unsubstituted aromatic hydrocarbon group. Examples of the substituent of the aliphatic hydrocarbon group include an ester group, an ether group, an amide group, and a halogen atom, and examples of the substituent of the aromatic hydrocarbon group include an alkyl group such as a methyl group or an ethyl group.
[0043] Examples of the carbonic acid diester represented by the formula (4) include diphenyl carbonate (hereinafter sometimes abbreviated as "DPC"), substituted diphenyl carbonate such as ditolyl carbonate, and dialkyl carbonate such as dimethyl carbonate, diethyl carbonate, and di-tert-butyl carbonate. Of these, preferred are diphenyl carbonate and substituted diphenyl carbonate, and particularly preferred is diphenyl carbonate (DPC).
[0044] The carbonate diester may contain impurities such as chloride ions, and these impurities may inhibit the polymerization reaction or deteriorate the hue of the resulting resin. Therefore, it is preferable to use a diester that has been purified, as necessary, by distillation or the like.
[0045] [Manufacturing method of polycarbonate resin] The polycarbonate resin of the present invention can be synthesized by a process of polycondensation reaction by transesterification using as raw materials at least a dihydroxy compound forming the structural unit (A) represented by the formula (1), a dihydroxy compound forming the structural unit (B) represented by the formula (2), a dihydroxy compound forming the structural unit (C), and a monomer containing a carbonic acid diester. More specifically, the polycarbonate resin can be obtained by removing, from the system, a monohydroxy compound and the like that are by-produced in the transesterification reaction in addition to the polycondensation.
[0046] In this step, specific examples of the dihydroxy compound forming the structural unit (A), the dihydroxy compound forming the structural unit (B), and the dihydroxy compound forming the structural unit (C) are the same as those described above. In particular, it is preferable that the dihydroxy compound forming the structural unit (B) is polytrimethylene ether glycol (PO3G), and the number average molecular weight of the polytrimethylene ether glycol is 1200 or more and 5000 or less. The lower limit is more preferably 1500 or more, and particularly preferably 1700 or more. The upper limit is more preferably 4000 or less, and particularly preferably 3000 or less. When the number average molecular weight of PO3G is within the above range, the structural unit (B) that becomes the soft segment forms a microphase separation structure in the resin, and further, since it has a moderate compatibility with the structural unit (A), adhesion at the phase interface is obtained, and excellent impact resistance can be expressed. The number average molecular weight of PO3G is calculated from the analysis of the hydroxyl value described later.
[0047] The transesterification reaction proceeds in the presence of a transesterification reaction catalyst (hereinafter referred to as a "polymerization catalyst.") The type of polymerization catalyst can have a significant effect on the reaction rate of the transesterification reaction and the quality of the resulting polycarbonate resin.
[0048] The polymerization catalyst is not particularly limited as long as it satisfies the transparency, color tone, heat resistance, weather resistance, and mechanical properties of the resulting polycarbonate resin. For example, metal compounds of Group 1 or Group 2 (hereinafter simply referred to as "Group 1" and "Group 2") in the long-form periodic table, as well as basic compounds such as basic boron compounds, basic phosphorus compounds, basic ammonium compounds, and amine compounds can be used as the polymerization catalyst, and among these, Group 1 metal compounds and / or Group 2 metal compounds are preferred.
[0049] Examples of the Group 1 metal compound include the following compounds: sodium hydroxide, potassium hydroxide, lithium hydroxide, cesium hydroxide, sodium hydrogen carbonate, potassium hydrogen carbonate, lithium hydrogen carbonate, cesium hydrogen carbonate, sodium carbonate, potassium carbonate, lithium carbonate, cesium carbonate, sodium acetate, potassium acetate, lithium acetate, cesium acetate, sodium stearate, potassium stearate, lithium stearate, cesium stearate, sodium borohydride, potassium borohydride, lithium borohydride, cesium borohydride, sodium phenylborohydride, and boron phenylide. Potassium, lithium phenyl boron, cesium phenyl boron, sodium benzoate, potassium benzoate, lithium benzoate, cesium benzoate, disodium hydrogen phosphate, dipotassium hydrogen phosphate, dilithium hydrogen phosphate, dicesium hydrogen phosphate, disodium phenylphosphate, dipotassium phenylphosphate, dilithium phenylphosphate, dicesium phenylphosphate, alcoholates, phenolates of sodium, potassium, lithium, and cesium, and disodium salts, dipotassium salts, dilithium salts, and dicesium salts of bisphenol A. As the Group 1 metal compound, lithium compounds are preferred from the viewpoints of polymerization activity and the color tone of the resulting polycarbonate resin.
[0050] Examples of the Group 2 metal compound include the following compounds: calcium hydroxide, barium hydroxide, magnesium hydroxide, strontium hydroxide, calcium hydrogen carbonate, barium hydrogen carbonate, magnesium hydrogen carbonate, strontium hydrogen carbonate, calcium carbonate, barium carbonate, magnesium carbonate, strontium carbonate, calcium acetate, barium acetate, magnesium acetate, strontium acetate, calcium stearate, barium stearate, magnesium stearate, and strontium stearate. As the Group 2 metal compound, magnesium compounds, calcium compounds, or barium compounds are preferred, and from the viewpoints of polymerization activity and color tone of the resulting polycarbonate resin, magnesium compounds and / or calcium compounds are more preferred, and calcium compounds are most preferred.
[0051] Although it is possible to use a basic compound such as a basic boron compound, a basic phosphorus compound, a basic ammonium compound, or an amine compound in combination with the Group 1 metal compound and / or the Group 2 metal compound, it is more preferable to use only the Group 1 metal compound and / or the Group 2 metal compound, and from the viewpoint of the color tone of the obtained polycarbonate resin, it is most preferable to use only the Group 2 metal compound.
[0052] The lower limit of the amount of the polymerization catalyst used is preferably 0.1 μmol or more, more preferably 0.5 μmol or more, and particularly preferably 1 μmol or more per mol of the total dihydroxy compounds used in the reaction.The upper limit of the amount of the polymerization catalyst used is preferably 300 μmol or less, more preferably 100 μmol or less, and particularly preferably 50 μmol or less per mol of the total dihydroxy compounds used in the reaction.
[0053] By adjusting the amount of the polymerization catalyst used within the above range, the polymerization rate can be increased, and therefore it is possible to obtain a polycarbonate resin with a desired molecular weight without necessarily increasing the polymerization temperature, and therefore it is possible to suppress deterioration in the color tone of the polycarbonate resin. In addition, it is possible to prevent the unreacted raw materials from volatilizing during the polymerization, which would cause the molar ratio of the dihydroxy compound and the carbonic acid diester to be lost, and therefore it is possible to more reliably obtain a resin with a desired molecular weight and copolymerization ratio. Furthermore, it is possible to suppress the occurrence of side reactions, and therefore it is possible to further prevent deterioration in the color tone of the polycarbonate resin or coloring during molding.
[0054] Considering the adverse effect of sodium, potassium, and cesium among the group 1 metals on the color tone of the polycarbonate resin, and the adverse effect of iron on the color tone of the polycarbonate resin, the total content of sodium, potassium, cesium, and iron in the polycarbonate resin is preferably 1 weight ppm or less. In this case, the deterioration of the color tone of the polycarbonate resin can be further prevented, and the color tone of the polycarbonate resin can be further improved. From the same viewpoint, the total content of sodium, potassium, cesium, and iron in the polycarbonate resin is more preferably 0.5 weight ppm or less. These metals may be mixed in not only from the catalyst used but also from the raw materials or reaction equipment. Regardless of the source, the total amount of these metal compounds in the polycarbonate resin is preferably within the above-mentioned range as the total content of sodium, potassium, cesium and iron.
[0055] The method of polycondensing a dihydroxy compound and a carbonic acid diester is carried out in multiple stages using multiple reactors in the presence of the above-mentioned catalyst. The reaction may be carried out in a batchwise manner, a continuous manner, or a combination of a batchwise manner and a continuous manner, but it is preferable to adopt a continuous manner, which is excellent in productivity and can obtain a polycarbonate resin with less heat history.
[0056] From the viewpoint of controlling the polymerization rate and the quality of the resulting polycarbonate resin, it is important to appropriately select the jacket temperature, the internal temperature, and the pressure in the reaction system according to the reaction stage. Specifically, it is preferable to obtain a prepolymer at a relatively low temperature and low vacuum in the early stage of the polycondensation reaction, and to increase the molecular weight to a predetermined value at a relatively high temperature and high vacuum in the later stage of the reaction. In this case, the distillation of unreacted monomers is suppressed, and it becomes easier to adjust the molar ratio of the dihydroxy compound and the carbonate diester to a desired ratio. As a result, the decrease in the polymerization rate can be suppressed. In addition, it becomes possible to more reliably obtain a polymer having a desired molecular weight and terminal group.
[0057] By adjusting the temperature of the polycondensation reaction, it is possible to improve productivity and prevent the increase of the heat history of the product. Furthermore, it is possible to further prevent the volatilization of the monomer and the decomposition and coloration of the polycarbonate resin. Specifically, the following conditions can be adopted as the reaction conditions in the first stage reaction. That is, the maximum temperature inside the polymerization reactor is set in the range of usually 160 to 230°C, preferably 180 to 220°C, and more preferably 190 to 215°C. In addition, the pressure of the polymerization reactor (hereinafter, pressure refers to absolute pressure) is set in the range of usually 1 to 110 kPa, preferably 5 to 50 kPa, and more preferably 7 to 30 kPa. In addition, the reaction time is set in the range of usually 0.1 to 10 hours, preferably 1 to 5 hours. It is preferable that the first stage reaction is carried out while distilling off the generated monohydroxy compound outside the reaction system.
[0058] From the second stage onwards, it is preferable to gradually reduce the pressure of the reaction system from the pressure of the first stage, and to finally reduce the pressure (absolute pressure) of the reaction system to 1 kPa or less while removing the monohydroxy compound that is subsequently generated from the reaction system. The maximum internal temperature of the polymerization reactor is usually set in the range of 200 to 260°C, preferably 210 to 240°C, and particularly preferably 215 to 235°C. The reaction time is usually set in the range of 0.1 to 10 hours, preferably 0.5 to 5 hours, and particularly preferably 1 to 3 hours.
[0059] Using the stirring power as an indicator, once it has been confirmed that the specified melt viscosity (molecular weight) has been reached, the polymerization reaction is stopped by introducing nitrogen into the reactor to return the pressure to normal pressure, or by withdrawing the molten resin from the reactor. The molten resin is discharged from the die head in the form of strands, cooled and solidified, and pelletized using a rotary cutter or the like. If necessary, extrusion devolatilization, extrusion kneading, and extrusion filtration processes may be added before pelletization. In these processes, additives are mixed into the resin, low molecular weight components are devolatilized using a vacuum vent, and foreign matter is removed using a polymer filter.
[0060] [Additives] Examples of additives that can be used within the range not impairing the effects of the present invention include antioxidants, heat stabilizers, light stabilizers, ultraviolet absorbers, fillers and other fillers, neutralizing agents, lubricants, antifogging agents, antiblocking agents, slip agents, dispersants, colorants, flame retardants, antistatic agents, conductivity imparting agents, crosslinking agents, crosslinking assistants, metal deactivators, molecular weight regulators, antibacterial agents, antifungal materials, fluorescent brightening agents, and light diffusing agents such as organic diffusing agents and inorganic diffusing agents. These additives can be used within the range not impairing the effects of the present invention.
[0061] [Characteristics of polycarbonate resin] Biomass ratio The biomass degree of a polycarbonate resin is defined as the weight ratio of structural units synthesized from plant-derived resources among all structural units constituting the polycarbonate resin. The polycarbonate resin of the present invention preferably has a biomass degree of 55% by weight or more, particularly preferably 60% by weight or more. In the examples described below, ISB and PO3G synthesized from plant-derived resources are used, and the other CHDM and DPC are synthesized from fossil resources, so the biomass degree of the polycarbonate resin synthesized using these is the sum of the weight ratios of the structural units derived from ISB and the structural units derived from PO3G.
[0062] Melt Viscosity The melt viscosity of the polycarbonate resin of the present invention is preferably 1000 Pa·s or more and 8000 Pa·s or less. The lower limit is more preferably 1500 Pa·s or more, and particularly preferably 2000 Pa·s or more. The upper limit is more preferably 6000 Pa·s or less, and particularly preferably 4000 Pa·s or less. Within the above range, the resin can have an excellent balance between mechanical properties and fluidity. In this specification, the melt viscosity is measured using a capillary rheometer (manufactured by Toyo Seiki Seisakusho) at a temperature of 220°C and a shear rate of 91.2 sec -1 The method for measuring the melt viscosity will be described in detail later.
[0063] Glass transition temperature The glass transition temperature of the polycarbonate resin of the present invention is preferably 90°C or higher and 140°C or lower. The lower limit is more preferably 100°C or higher, particularly preferably 110°C or higher. The upper limit is more preferably 135°C or lower, particularly preferably 130°C or lower. Within the above range, the polycarbonate resin can be applied to a wide range of applications, can be easily melt-processed, and can easily achieve good mechanical properties such as impact resistance. The method for measuring the glass transition temperature will be described later in detail. The glass transition temperature of the polycarbonate resin can be appropriately adjusted, for example, by selecting the weight ratio of the structural unit (A), the structural unit (B), and the structural unit (C) or the type of monomer into which each structural unit is introduced.
[0064] Impact strength The polycarbonate resin of the present invention has an Izod impact value of 20 kJ / m as measured by the method described below. 2 It is preferable that the concentration is 25 kJ / m or more. 2 When the content is within the above range, the material has sufficiently high impact resistance strength, and can be used for applications such as automobile interior parts that require high impact resistance properties, and for molded products having fitting parts that are prone to breakage due to stress concentration.
[0065] [Polycarbonate resin composition] The polycarbonate resin of the present invention can be kneaded with one or more of the following resins, for example: polycarbonate, aromatic polyester, aliphatic polyester, polyamide, polystyrene, polyolefin, amorphous polyolefin, acrylic resin, acrylonitrile-butadiene-styrene copolymer (ABS resin), acrylonitrile-styrene copolymer (AS resin), etc.; elastomers such as acrylic rubber and butadiene rubber; and biodegradable resins such as polylactic acid and polybutylene succinate, etc., within the scope of the present invention that does not impair the effects of the present invention. Among these, from the viewpoint of excellent impact resistance and transparency of the resin composition, it is preferable to contain acrylic rubber, and more preferably to contain acrylic rubber having a core-shell structure. Among these, alkyl acrylate-alkyl methacrylate-styrene copolymer is particularly preferable.
[0066] [Method of producing resin composition] The resin composition can be produced, for example, by a method of mechanically melt-kneading each of the above-mentioned components constituting the resin composition. As the melt kneader, for example, a single screw extruder, a twin screw extruder, a Brabender, a Banbury mixer, a kneader blender, a roll mill, etc. can be used. In kneading, each component may be kneaded at once, or a multi-stage division kneading method in which an arbitrary component is kneaded and then the remaining components are added and kneaded may be used. Among them, a method in which each component is continuously charged using a twin screw extruder equipped with a vacuum vent and a resin composition is continuously obtained is preferable from the viewpoint of productivity and quality uniformity. The lower limit of the kneading temperature is usually 150°C or more, preferably 180°C or more, and more preferably 200°C or more. The upper limit of the kneading temperature is usually 280°C or less, preferably 260°C or less, more preferably 250°C or less, and particularly preferably 240°C or less. Within this range, productivity (processing speed of kneading) can be increased while suppressing heat deterioration due to heating by the kneader and heat generation due to shear.
[0067] [Method of manufacturing molded products] The polycarbonate resin of the present invention can be processed into various molded products by molding methods such as injection molding (insert molding, two-color molding, sandwich molding, gas injection molding, etc.), extrusion molding, inflation molding, T-die film molding, lamination molding, blow molding, hollow molding, compression molding, and calendar molding. The shape of the molded product is not particularly limited, and examples thereof include sheets, films, plates, particles, lumps, fibers, rods, porous bodies, and foams, and are preferably sheets, films, and plates. The molded film can also be uniaxially or biaxially stretched. Examples of stretching methods include roll method, tenter method, and tubular method. Furthermore, surface treatments such as corona discharge treatment, flame treatment, plasma treatment, and ozone treatment, which are usually used industrially, can also be performed.
[0068] [Application] Although there is no particular limitation on the uses, since the polycarbonate resin of the present invention has excellent weather resistance in addition to mechanical strength, it is particularly suitable for use in interior and exterior components of automobiles, building materials used outdoors (lighting covers, carports, highway soundproofing walls, etc.), housings for electric and electronic devices, and containers for food and cosmetics, etc. EXAMPLES
[0069] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples as long as the gist of the present invention is not exceeded.
[0070] [Measurement method] Various physical properties were measured according to the following methods.
[0071] Number average molecular weight and average degree of polymerization (n) of polytrimethylene ether glycol (PO3G) The hydroxyl value of polytrimethylene ether glycol was measured by a method using an acetylation reagent in accordance with JIS K1557-1. The number average molecular weight and average degree of polymerization (n) were calculated from the hydroxyl value using the following formula. Number average molecular weight = 1 / (hydroxyl value / 1000 / 56.11 / 2) -Hydroxyl value unit: mg-KOH / g-polymer 56.11: Molecular weight of calcium hydroxide (KOH) Average degree of polymerization=(number average molecular weight-1.0×2-16.0) / 58.1 1.0: Molecular weight of hydrogen atom 16.0: Molecular weight of oxygen atom 58.1: Molecular weight of the repeating unit of polytrimethylene ether glycol (C3H6O)
[0072] Biomass ratio The sum of the weight ratios of the structural units derived from ISB and the structural units derived from PO3G represents the biomass ratio of the polycarbonate resin.
[0073] Melt Viscosity The pellet-shaped resin was vacuum dried at 100°C for 5 hours or more. The melt viscosity of the pellet was then measured using a capillary rheometer (manufactured by Toyo Seiki Co., Ltd.). An orifice of 1 mmφ×10 mmL was used, the temperature was 220°C, and the shear rate was 6.08 to 1824 sec -1 The measurements were performed at a shear rate of 91.2 sec -1 The value at is the melt viscosity of the resin to be measured.
[0074] Glass transition temperature The glass transition temperature was measured using a differential scanning calorimeter DSC6220 (manufactured by SII NanoTechnology). Approximately 10 mg of the resin was placed in an aluminum pan manufactured by the same company and sealed. Measurement was started at 200°C under a nitrogen gas flow of 50 mL / min, and the temperature was cooled to 30°C at a rate of 20°C / min. The temperature was held at 30°C for 3 minutes, and then the temperature was raised again to 200°C at a rate of 20°C / min. From the DSC data during the temperature rise, the extrapolated glass transition onset temperature, which is the temperature at the intersection of a straight line extending the low-temperature baseline to the high-temperature side and a tangent drawn at the point where the gradient of the curve of the step-like change in the glass transition is maximum, was calculated and used as the glass transition temperature.
[0075] Izod impact strength The resin pellets were vacuum dried at 90°C for 5 hours or more, and then an Izod test specimen was prepared using a small injection molding machine C, Mobile-0813 (manufactured by Shinko Selvic Co., Ltd.). A notch with a tip radius of 0.25 mm was made in the test specimen using a cutter. In accordance with ASTM D256, the Izod impact strength (unit: kJ / m) was measured at 23°C using a notched test specimen with a thickness of 3.2 mm. 2 The higher the Izod impact strength value, the better the impact resistance.
[0076] (Raw materials used) The abbreviations and manufacturers of the compounds used in the following Examples and Production Examples are as follows. [Dihydroxy compounds] ISB: Isosorbide (manufactured by Rocket Fleuret) PO3G2000: Polytrimethylene ether glycol, number average molecular weight measurement value 2005 (Allessa, product name: VELVETOL) PO3G1000: Polytrimethylene ether glycol, number average molecular weight measured: 1043 (Allessa) PO3G500: Polytrimethylene ether glycol, number average molecular weight 514 (Allessa) CHDM: 1,4-cyclohexanedimethanol (SK Chemical) [Carbonate diester] DPC: Diphenyl carbonate (Mitsubishi Chemical Corporation) [Impact resistance improvement material] Acrylic core-shell rubber: butyl acrylate-methyl methacrylate-styrene copolymer (core: butyl acrylate, shell: methyl methacrylate, styrene)
[0077] Example 1 Polymerization was carried out using a batch polymerization apparatus consisting of two vertical stirring reactors equipped with stirring blades and reflux condensers. The polymerization mixture consisted of 56.65 parts by weight (0.388 mol) of ISB, 4.94 parts by weight (0.002 mol) of PO3G2000, 23.96 parts by weight (0.166 mol) of CHDM, 119.15 parts by weight (0.556 mol) of DPC, and 2.94 × 10 calcium acetate monohydrate as a catalyst. -4 Part by weight (1.67×10 -6 mol) was charged into the reactor. After the inside of the reactor was substituted with nitrogen under reduced pressure, heating was performed with a heat medium, and stirring was started when the inside temperature reached 100 ° C. 40 minutes after the start of the temperature increase, the inside temperature was reached 210 ° C., and while controlling to maintain this temperature, the pressure was simultaneously reduced, and 90 minutes after reaching 210 ° C., the pressure was reduced to 13.3 kPa. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 110 ° C., a small amount of monomer components contained in the phenol vapor were returned to the reactor, and the uncondensed phenol vapor was led to a condenser at 45 ° C. and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was set to 220 ° C. and the pressure was set to 20 kPa in 40 minutes. Thereafter, the polymerization was allowed to proceed while further reducing the pressure until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the polycarbonate produced was extruded into water and the strands were cut to obtain pellets. The results of the various evaluations mentioned above are shown in Table 1. In Table 1, the percentage (wt%) of each component in the column for polycarbonate resin indicates the percentage (weight ratio) of structural units derived from each component constituting the polycarbonate resin. This also applies to the following examples and comparative examples.
[0078] Example 2 The raw materials were ISB 53.67 parts by weight (0.367 mol), PO3G2000 9.87 parts by weight (0.005 mol), CHDM 22.70 parts by weight (0.157 mol), DPC 113.43 parts by weight (0.530 mol), calcium acetate monohydrate 2.80 × 10 -4 Part by weight (1.59×10 -6The same procedure as in Example 1 was repeated except that the reaction mixture was changed to (mol).
[0079] Comparative Example 1 The raw materials were 84.90 parts by weight (0.581 mol) of ISB, 126.94 parts by weight (0.593 mol) of DPC, and 1.54 × 10 calcium acetate monohydrate. -4 Weight part (8.71×10 -7 The same procedure as in Example 1 was repeated except that the polymerization temperature was 230° C. and the final polymerization temperature was 230° C.
[0080] Comparative Example 2 The raw materials were ISB 80.65 parts by weight (0.552 mol), PO3G2000 4.94 parts by weight (0.002 mol), DPC 119.94 parts by weight (0.560 mol), calcium acetate monohydrate 2.93 × 10 -4 Part by weight (1.66×10 -6 The same procedure as in Example 1 was repeated except that the polymerization temperature was 230° C. and the final polymerization temperature was 230° C.
[0081] Comparative Example 3 The raw materials were ISB 75.56 parts by weight (0.517 mol), PO3G500 10.47 parts by weight (0.020 mol), DPC 115.70 parts by weight (0.540 mol), calcium acetate monohydrate 2.84 × 10 -4 Part by weight (1.61×10 -6 The same procedure as in Example 1 was repeated except that the reaction mixture was changed to (mol).
[0082] Comparative Example 4 The raw materials were ISB 70.47 parts by weight (0.482 mol), PO3G500 16.18 parts by weight (0.031 mol), DPC 110.58 parts by weight (0.516 mol), calcium acetate monohydrate 9.05 × 10 -4 Weight part (5.14×10 -6 The same procedure as in Example 1 was repeated except that the reaction mixture was changed to (mol).
[0083] Comparative Example 5 The raw materials were 59.63 parts by weight (0.408 mol) of ISB, 25.22 parts by weight (0.175 mol) of CHDM, 126.12 parts by weight (0.589 mol) of DPC, and 1.54 × 10 calcium acetate monohydrate. -4 Weight part (8.74×10 -7 The same procedure as in Example 1 was repeated except that the reaction mixture was changed to (mol).
[0084] Comparative Example 6 The raw materials were ISB 56.65 parts by weight (0.388 mol), PO3G1000 4.88 parts by weight (0.005 mol), CHDM 23.96 parts by weight (0.166 mol), DPC 119.63 parts by weight (0.558 mol), calcium acetate monohydrate 2.95 × 10 -4 Part by weight (1.68×10 -6 The procedure of Example 1 was repeated except that the reaction mixture was changed to (mol).
[0085] Comparative Example 7 The raw materials were ISB 56.65 parts by weight (0.388 mol), PO3G500 4.76 parts by weight (0.009 mol), CHDM 23.96 parts by weight (0.166 mol), DPC 120.61 parts by weight (0.563 mol), calcium acetate monohydrate 2.98 × 10 -4 Part by weight (1.69×10 -6 The procedure of Example 1 was repeated except that the reaction mixture was changed to (mol).
[0086] Comparative Example 8 The raw materials were ISB 53.67 parts by weight (0.367 mol), PO3G500 9.52 parts by weight (0.019 mol), CHDM 22.70 parts by weight (0.157 mol), DPC 116.35 parts by weight (0.543 mol), calcium acetate monohydrate 2.87 × 10 -4 Part by weight (1.63×10 -6 The procedure of Example 1 was repeated except that the reaction mixture was changed to (mol).
[0087] Comparative Example 9 90 parts by weight of the polycarbonate resin pellets obtained in Comparative Example 5 were blended with 10 parts by weight of an acrylic core-shell rubber as an impact resistance improver, and then extrusion kneading was carried out at a cylinder temperature of 240°C and an extrusion rate of 12 kg / hr using a twin-screw extruder TEX30HSS (manufactured by Japan Steel Works, Ltd.) equipped with a vacuum vent to obtain pellets of a polycarbonate resin composition. The obtained polycarbonate resin composition was subjected to the various evaluations described above.
[0088] [Table 1]
Claims
1. A polycarbonate resin comprising at least a structural unit (A) represented by the following formula (1), a structural unit (B) represented by the following formula (2), and a structural unit (C) derived from an aliphatic dihydroxy compound and / or an alicyclic dihydroxy compound, A polycarbonate resin containing 40% by weight or more and 80% by weight or less of the structural unit (A) and 1% by weight or more and 20% by weight or less of the structural unit (B), wherein the number average molecular weight of the structural unit (B) is 1,200 or more and 5,000 or less. 【Chemistry 1】 【Chemistry 2】 In formula (2), n is an integer of 2 or more.
2. The polycarbonate resin according to claim 1 , containing the structural unit (C) in an amount of 1% by weight or more and 40% by weight or less.
3. The polycarbonate resin according to claim 1 or 2, which contains, as the structural unit (C), 1 wt % or more and 40 wt % or less of a structural unit represented by the following formula (3): 【Chemistry 3】
4. The polycarbonate resin according to any one of claims 1 to 3, having a glass transition temperature of 90°C or higher and 140°C or lower.
5. A molded article obtained by molding the polycarbonate resin according to any one of claims 1 to 4.
6. A method for producing the polycarbonate resin according to any one of claims 1 to 4, comprising a step of polycondensing raw materials, by transesterification, a dihydroxy compound forming the structural unit (A) represented by formula (1), a dihydroxy compound forming the structural unit (B) represented by formula (2), a dihydroxy compound forming the structural unit (C), and a monomer containing a carbonate diester; In the step, the dihydroxy compound that forms the structural unit (B) represented by the formula (2) is polytrimethylene ether glycol, and the number average molecular weight of this polytrimethylene ether glycol is 1,200 or more and 5,000 or less.
Citation Information
Patent Citations
Polyester copolymer and molded article
JP2007112821A
Copolycarbonate
JP2011241277A
Thermoplastic resin composition and molded article using the same
JP2017088774A
Polycarbonate resin, and polycarbonate resin composition
JP2021091900A
Polycarbonate and process for producing the same
WO2004111106A1